KEPEMIMPINAN TRANSFORMASIONAL DAN PENGARUHNYA TERHADAP INOVASI KURIKULUM SERTA KINERJA DOSEN DI PERGURUAN TINGGI SWASTA KALIMANTAN TIMUR - Bambang Styawan; Sri Hayati; Anastasia Hiyang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the direct and indirect effects of Transformational Leadership (TL) among leaders of Private Universities (PTS) in East Kalimantan on Lecturer Performance (LP), with Curriculum Innovation (CI) serving as a mediating variable. Private universities in East Kalimantan face significant challenges in adapting to the Merdeka Belajar–Kampus Merdeka (MBKM) policy and increasing regional competitiveness, making TL a critical factor. This research employs a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with a sample of lecturers from private universities in East Kalimantan. Preliminary findings indicate that TL significantly and positively drives CI, and CI strongly correlates with LP. The study concludes that inspirational and motivational TL is a key prerequisite for fostering creative curriculum adaptation and enhancing lecturer productivity. TL influences LP not only directly but also indirectly through creating an environment that supports CI. Recommendations are proposed for university leaders to strengthen the dimensions of Intellectual Stimulation and Idealized Influence.Keywords: keyword 1, keyword 2, keyword 3 Keywords: Transformational Leadership, Curriculum Innovation, Lecturer Performance, Private Universities, East Kalimantan